Relationship between digital banking and financial inclusion: Evidence from Tunisia - Gharbi, Inés; Kammoun, Aida (Sekolah Tinggi Manajemen IPMI, 2022)
The concept of financial inclusion emerged in the period from the 1990s to 2000. It has been considered a policy priority by governments and international organizations to reduce poverty and establish inclusive growth. The Tunisian government and the Central Bank of Tunisia have taken some measures to promote financial inclusion through digitalization, such as Automated Teller Machine, mobile banking, internet banking and e-wallets. Within this framework, our study examines the relationship between the digitization of the Tunisian banking sector and financial inclusion and whether technological developments in Fintech have contributed to an inclusive financial system. By developing a questionnaire survey of Tunisian bank employees, we find a significant positive relationship between digital technology and financial inclusion. Our research is original in that it examines the relationship between digital banking and financial inclusion using four inclusive development indicators: access, use, quality, and efficiency of financial services. Likewise, and to our knowledge, this is the first study of its kind in the Tunisian context.